Оценивание неопределенности измерений при проведении калибровок мер - Сачева, Е. Н. (ХНУРЭ, 2009)
The uncertainty evaluations for three versions of measurements methods used at calibrations of material measures is made
Keywords: неопределенность измерений; проведение калибровок мер